A tool for the interpretation of the organizational totems: Juan Valdez® case - Pilar Valencia-De Lara, Manuela Escobar-Sierra, Felipe Calderón-Valencia, (Opción, 2019)
The totem represents an external and visible expression that constitutes as a symbol of the group. The objective of the study is to propose a tool for organizational management by interpreting totems. This tool is verified in the case of Procafecol –Juan Valdez® owner- that has supported in its totem and in environmental, legal and ethical policies, to transform perception of its stakeholders -being recognized among largest coffee producers (1959), competing with cafeterias (2002) and relaunching its internationalization (2012)-. Showing how management of totem is an intermediate point between reference totem -associated with discredit- and organizational totem -associated with reputation-